The Role of International Marketing in Attracting Foreign Investment and Enhancing Economic Relations - Abuojaylah Wannees Omar; Omaran Aun Allah Milad, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
The objective of this research is to investigate the strategic role of international marketing in attracting Foreign Direct Investment (FDI) and fostering robust international economic relations. In an increasingly globalized marketplace, nations must differentiate themselves to secure capital inflows. This study explores how international marketing frameworks, including nation branding, targeted promotional strategies, and digital diplomacy, serve as catalysts for investor interest. By analyzing the synergy between marketing communication and economic stability, the research identifies that effective marketing not only highlights a country’s competitive advantages but also mitigates perceived risks for foreign investors. The methodology employs a qualitative systematic review of existing literature and case studies to evaluate the impact of marketing initiatives on FDI trends. Findings suggest that countries utilizing sophisticated international marketing strategies experience higher levels of investor confidence and more sustainable economic partnerships. Furthermore, the study highlights the necessity of aligning marketing messages with actual structural reforms to ensure long-term credibility. The research concludes that international marketing is no longer a peripheral activity but a core component of national economic policy, essential for navigating the complexities of the global economy and building enduring bilateral and multilateral ties.
Keywords: International Marketing; Foreign Direct Investment (FDI); Economic Relations; Nation Branding; Global Trade; Investment Promotion